Selenium inclusion decreases oxidative stress indicators and muscle injuries in sea bass larvae fed high-DHA microdiets - Betancor, Mónica B.; Caballero, M. José; Terova, Genciana; Saleh, Reda; Atalah, Eyad; Benítez-Santana, Tibiábin; Bell, J. Gordon; Izquierdo, Marisol (British Journal of Nutrition, 2012)
The objective of the present study was to determine the effect of Se inclusion in high-DHA and vitamin E microdiets (5 g DHA/100 g dry weight and 300 mg vitamin E/100 g dry weight; 5 g DHA/100 g dry weight and 300 mg vitamin E/100 g dry weight supplemented with Se) in comparison with a control diet (1 g DHA/100 g dry weight and 150 mg vitamin E/100 g dry weight) on sea bass larval growth, survival, biochemical composition, malonaldehyde (MDA) content, muscle morphology and antioxidant enzymes (AOE), insulin-like growth factors (IGF) and myosin expression. For a given DHA and vitamin E dietary content, Se inclusion favoured larval total length and specific growth rate, and reduced the incidence of muscular lesions, MDA contents and AOE gene expression. In contrast, IGF gene expression was elevated in the 5/300 larvae, suggesting an increased muscle mitogenesis that was corroborated by the increase in mRNA copies of myosin heavy chain. The results of the present study denoted the beneficial effect of Se not only in preventing oxidative stress, as a glutathione peroxidase cofactor, but probably due to other as yet unknown physiological functions. 2128 2115 4 1,292 3,302 Q1 Q1 SCIE